Positioning Strategies of Polish Political Parties in the 2014 European Parliament Election - Cichosz, Marzena (Political Preferences, 2014)
The article concerns an analysis of the types of positioning an electoral agenda adopted by the Polish political parties during the political campaign before the elections to the European Parliament in 2014. Positioning the electoral offer has been treated as one of the main elements of the electoral strategies of political parties, as the way of defining their electoral goals and identifying their strengths and weaknesses as well as opportunities and threats. The scope of analysis assumes main Polish political parties represented in the Polish parliament in the years 2011 - 2014 and additionally the party that managed to cross the entry barrier into the parliamentary market in the EP election in 2014.